Beyond parliament : human rights and the politics of social change in the global south - Chitonge, Horman (Nijhoff law specials, 2015)
In Beyond Parliament Horman Chitonge offers a unique combination of the conceptual dimensions with the practical examples of human rights discourse deployed as an instrument for social change in the global south. He uses the right to water and the right to food to illustrate that human rights are never given on a silver platter; giving effect to human rights is always an outcome of a continuous struggle to protect human dignity and value. To implement this view of human rights, the book argues, requires going beyond the parliamentary politics of recognising and acknowledging human rights in statutes and bill of rights to the radical democratic politics of giving effect to the recognised rights, especially among the poor and marginalised.